개발신탁수익권의 가치평가 필요성 - 김종서; Jong Seo Kim (감정평가학 논집, 2013)
신탁수익권은 재산권임에도 불구하고 신탁법 시행이전에는 법적근거의 부족으로 그 활용이 저조하였다. 신탁법이 시행되어 신탁수익권에 대한 법적근거가 명확하게 되었다. 또한 .동산 . 채권 등의 담보에 관한 법률.의 시행으로 부동산 이외의 재산권도 담보목적물로 제공하여 필요자금을 조달할 수 있게 되었다. 본 연구의 목적은 ⅰ) 개발신탁사업의 신탁수익권 발행규모를 추산하여 경제적 효용성을 파악하고, ⅱ) 사업진행단계별 개발신탁수익권의 가치변화, ⅲ) 개발신탁수익권이 감정평가의 대상임을 밝히고, ⅳ) 판례를 통하여 개발신탁수익권의 평가주체를 밝히는 것이다. 연구 결과 ⅰ) 법원은 “가치평가”의 주체는 전문적 자격 있는 평가인인 감정평가업자임을 명확하게 선고하였고, ⅱ) 개발신탁수익권이 부동산을 기초로 하는 권리임이 명백하며, ⅲ) 동채법상 담보제공의 목적물에 포함됨이 명확하고, ⅳ) 그 발행규모 또한 적지 않아 시장성이 있고, ⅴ) 개발신탁수익권의 유동화를 갈망하는 현 상황에서 .부동산 가격공시 및 감정평가에 관한 법률). 상 감정평가업자가 개발신탁수익권의 공정가치 평가의 주체가 되는 것은 당연하다. The right of trust benefits had not been considered as a type of property rights due to lack of a legal basis, However, the implementation of the Trust Act made clear of its use. In addition, the enforcement of “Estate/bond of collateral law” not only used real estate as collateral but also other property rights as collateral in order to raise necessary funds. Major study objects are i) comprehending economic benefits by estimating the volume of issued the right of trust benefits for development projects, ii) a change in the valuation of the right of trust benefits in development projects, iii) clarify that the right of trust benefits in development projects should be appraised, iv) clarify that appraisal subject of the right of trust benefits in development projects by following the precedents. As a result i) the court clearly announced that appraisal business operators are the principal appraisal subject for “Appraisal”, ii) the right of trust benefits in development projects is clearly a legal right in real estate, iii) the law precisely states that the right of trust benefits in development projects are objects for provision of collateral, iv) presented issuance scale for the right of trust benefits in development projects has a high advantage in terms of marketablility, v) according to “Public Announcement for Real Estate Value and Appraisal Law”, it is resonable to state that the appraisal business operator is the appraisal subject for appraising the right of trust benefits in development projects.